2019
DOI: 10.1039/c8dt04491k
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen activation by a dinuclear thiolate-ligated Fe(ii) complex

Abstract: The activation of dioxygen by a dimeric Fe(ii) thiolate complex and the detection of an Fe(iii)–O2–Fe(iii) intermediate are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Whereas in the presence of O 2 the photodecomposed protein (species C) showed characteristic spectra in both UV–vis absorption and EPR spectroscopies similar to those of pf Rd-C9A-Fe III (Figure A,B), surprisingly, its molecular weight was measured to be ∼16 Da larger (Figure C) than that of pf Rd-C9A-Fe III . It was considered that this species may be derived from the oxidation of Cys (S-oxygenation) or iron (Fe III -O 2 – , Fe III -O 2 2– , Fe IV/V O), as previously reported. , The reaction of species C with dimedonea reagent for the selective detection of S-oxygenates , was carried out, but no product was detected by ESI-MS (data not shown). Further, substoichiometric peroxynitrite was detected upon irradiation under air (Figure S16), which might be the product of the reaction between superoxide (O 2 – ) and the released NO, as reported for other iron peroxynitrite complexes. , We thus tend to assign species C as the Fe III -O 2 – complex, and at this stage, no further effort was made to elucidate the identity of this intermediate species.…”
Section: Resultsmentioning
confidence: 72%
“…Whereas in the presence of O 2 the photodecomposed protein (species C) showed characteristic spectra in both UV–vis absorption and EPR spectroscopies similar to those of pf Rd-C9A-Fe III (Figure A,B), surprisingly, its molecular weight was measured to be ∼16 Da larger (Figure C) than that of pf Rd-C9A-Fe III . It was considered that this species may be derived from the oxidation of Cys (S-oxygenation) or iron (Fe III -O 2 – , Fe III -O 2 2– , Fe IV/V O), as previously reported. , The reaction of species C with dimedonea reagent for the selective detection of S-oxygenates , was carried out, but no product was detected by ESI-MS (data not shown). Further, substoichiometric peroxynitrite was detected upon irradiation under air (Figure S16), which might be the product of the reaction between superoxide (O 2 – ) and the released NO, as reported for other iron peroxynitrite complexes. , We thus tend to assign species C as the Fe III -O 2 – complex, and at this stage, no further effort was made to elucidate the identity of this intermediate species.…”
Section: Resultsmentioning
confidence: 72%
“…Comparing the length of these bonds with related bond lengths in hydrazone based ligands indicates that the lengths of these bonds are between the C-N and C=N bond lengths. [37] The lengths of C − S bonds are in the range of 1.759-1.776 Å which are within the normal range of C-S bonds, [38,39] indicating that this moiety adopts the thiol tautomeric form.…”
Section: Shake Flask Experimentsmentioning
confidence: 87%
“…Compared to the prevalent nitrogen ligands [9] like porphyrin and its analogues, sulfur ligands [10] are also concerned because of the high reactivity of their corresponding Fe IV =O species. Hsieh et al [11] revealed the thiolate-ligated Fe IV -oxo species as the transient intermediate for the hydride-transfer reaction. Deutscher et al [12] revealed that introducing sulfur ligands to replace two equatorial nitrogen ligands weakens the Fe=O bond and thus enhances the oxidative reactivity of the Fe IV =O unit.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the prevalent nitrogen ligands [9] like porphyrin and its analogues, sulfur ligands [10] are also concerned because of the high reactivity of their corresponding Fe IV =O species. Hsieh et al [11] . revealed the thiolate‐ligated Fe IV ‐oxo species as the transient intermediate for the hydride‐transfer reaction.…”
Section: Introductionmentioning
confidence: 99%